A review of various protein separation techniques and valorization of cheese whey and buttermilk - Sukmana Hadid (EUROPEAN FOOD RESEARCH AND TECHNOLOGY, 2025)
The dairy industry generates large quantities of nutrient-rich by-products, particularly cheese whey, and buttermilk, which are valuable sources of bioactive proteins and phospholipids. Whey proteins exhibit notable therapeutic potential, offering various health benefits such as antihypertensive effects, immune modulation, and opioid antagonism. Similarly, buttermilk-derived phospholipids demonstrate bioactive properties, including cholesterol reduction, anti-inflammatory activity, and neuroprotective effects. This review critically assesses recent advances in protein separation techniques, comparing conventional thermal methods, known to potentially compromise protein functionality, with emerging non-thermal approaches such as high-pressure processing and membrane filtration, which enable efficient recovery while preserving bioactivity. Additionally, advanced methodologies such as multi-level processing and enzymatic hydrolysis further expand the protein separation techniques. Key technical challenges, including high mineral content in whey and the low solids concentration in buttermilk, are discussed alongside potential innovative solutions. Whey's elevated mineral levels can reduce protein isolation efficiency and diminish the emulsifying properties of whey proteins, potentially restricting their functional applications. Meanwhile, the low total solids content in buttermilk poses challenges in achieving high protein concentration yields, requiring advanced separation techniques. Further, this review examines contemporary trends in cheese whey and buttermilk valorization, highlighting their opportunities for enhanced food applications. It also explores cross-sectoral utilization in biofuels, biodegradable materials, pharmaceuticals, and agriculture, supporting economic and sustainability goals in the dairy sector.